2017
DOI: 10.1016/j.jpedsurg.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of oesophageal atresia without or with proximal tracheooesophageal fistula – Gross types A and B

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Recent large studies have identified the prevalence of EA to be 2.3‐2.4 cases per 10 000 births . In the last decade, survival has increased to 91%‐98% . EA has a high incidence of associated anomalies, ranging from 31% to 59% .…”
Section: Introductionmentioning
confidence: 99%
“…Recent large studies have identified the prevalence of EA to be 2.3‐2.4 cases per 10 000 births . In the last decade, survival has increased to 91%‐98% . EA has a high incidence of associated anomalies, ranging from 31% to 59% .…”
Section: Introductionmentioning
confidence: 99%
“…From studies reporting endoscopic surveillance, in six patients gastric metaplasia preceded intestinal metaplasia on sequential endoscopies, with gastric metaplasia occurring 1–5 years prior 21 , 22 . While there were two reported cases of resolution of BO (1 gastric and 1 intestinal) either spontaneously or following anti-reflux treatment, the majority of cases of BO persisted 9 , 47 , 66 . Gastric and intestinal metaplasia were present concurrently at screening endoscopy in four patients 22 .…”
Section: Resultsmentioning
confidence: 97%
“…In a cohort of 31 patients with EA without fistula, Holland et al found long‐term sequelae in 67.7% of cases, with the need for multiple additional surgical procedures . In a long‐term outcome study, with a median follow‐up of 35 years (interquartile range, 7.4‐40 y), Koivusalo et al described high morbidity among survivors of EA types A and B . However, compared with the whole series from 1947 to 2014 (63%), they observed an excellent survival rate in the last years of the study (93% during the period 1985‐2014).…”
Section: Discussionmentioning
confidence: 99%